2023
DOI: 10.1002/jmv.29324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human herpesvirus‐8 viremia and antibody positivity in patients with HIV infection with human herpesvirus‐8‐related diseases

Dai Watanabe,
Shun Iida,
Kazuyuki Hirota
et al.

Abstract: Human herpesvirus‐8 (HHV‐8) viremia is associated with refractory conditions in patients infected with HIV‐1. Therefore, we evaluated the factors related to plasma HHV‐8‐DNA. Participants included patients infected with HIV‐1 who visited our hospital. Plasma HHV‐8‐DNA levels were measured using real‐time polymerase chain reaction, and anti‐HHV‐8 antibodies were assessed through enzyme immunoassays using multiple antigens (K8.1, ORF59, ORF65, and LANA). Factors related to plasma HHV‐8‐DNA were examined using Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Other studies have also reported the high seroprevalence (>90% detection rate) of anti-KSHV antibodies among patients with HIV-associated KS [ 26 ]. It has also been observed previously that ART initiation is associated with a rise in the plasma detection of anti-KSHV antibodies [ 27 ]. The continued antigenic stimulation by persistent KSHV detection and the fact that all our study participants were on ART for some time likely explains the high detection and titer of anti-KSHV antibodies in our cohort.…”
Section: Discussionmentioning
confidence: 61%
“…Other studies have also reported the high seroprevalence (>90% detection rate) of anti-KSHV antibodies among patients with HIV-associated KS [ 26 ]. It has also been observed previously that ART initiation is associated with a rise in the plasma detection of anti-KSHV antibodies [ 27 ]. The continued antigenic stimulation by persistent KSHV detection and the fact that all our study participants were on ART for some time likely explains the high detection and titer of anti-KSHV antibodies in our cohort.…”
Section: Discussionmentioning
confidence: 61%
“…Although HHV-8 viral loads were similar in tissues among the 2 KS groups, circulating levels of HHV-8 DNA (both in plasma and isolated PBMCs) were significantly lower in HIV KS than in cKS. A potential explanation for this observation is the higher anti–HHV-8 antibody levels found in HIV KS compared to cKS, which could neutralize circulating HHV-8 viruses but have a lower impact in tissues [ 18 , 19 ]. This hypothesis should be explored in further studies.…”
Section: Discussionmentioning
confidence: 99%